Development of a Health Promotion Model to Improve the Skill Levels of Posyandu Volunteers: A Systematic Literature Review - Kartini Kartini; Siwi Pramatama; Elveira Gamelia (Eduvest - Journal of Universal Studies, 2026)
Posyandu cadres play a strategic role in supporting community-based primary health services in Indonesia. However, increasingly complex public health challenges require cadres to have broader competencies beyond basic technical skills. Health promotion has been widely recognized as an effective approach to strengthening the capacity and skills of public health volunteers, but studies integrating various components of health promotion into a comprehensive cadre development model are limited. This research aims to identify and synthesize health promotion components that contribute to improving the competence and skills of public health volunteers and develop a health promotion model to improve the skill level of Posyandu cadres. The Systematic Literature Review was conducted following the PRISMA guidelines. Literature searches were conducted using Publish or Perish linked to the Google Scholar database with keywords ("public health volunteers") AND ("health promotion") AND ("competencies" OR "skills") AND ("model" OR "framework") for publications between 2020 and 2025. An initial search yielded 200 articles. After selecting titles, abstracts, and full texts based on predetermined inclusion and exclusion criteria, 15 articles were selected for qualitative synthesis. Thematic analysis is used to identify the main components of health promotion related to cadre competency development. The findings point to six key components that contribute to improving the competence and skills of public health volunteers: leadership development, capacity building, health literacy, health communication, community empowerment, and organizational and health system support. These components were consistently identified across the reviewed studies as important factors influencing cadre effectiveness, community participation, and sustainability of health promotion programs.